2005
DOI: 10.1159/000089125
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin-Dependent Regulation of Dendritic Cells in the Context of Autoimmune Responses

Abstract: Dendritic cells (DC) are professional antigen-presenting cells that are specialized in the uptake of antigens and their transport from peripheral tissues to the lymphoid organs. Because of their capacity to stimulate naïve T cells, DC have a central role in the initiation of primary immune responses and are considered promising tools and targets for immunotherapy. Investigating the signals that regulate the function of DC, the sentinels of the immune system, is also critical to understanding the role of DC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Accumulating evidence indicates that B lymphocytes exert regulatory effects on the antigen-presenting function of dendritic cells. Srini V. Kaveri and colleagues, France, have recently shown that natural antibodies sustain the differentiation and maturation of human dendritic cells, and focus in their review on the effects of therapeutic intravenous immunoglobulins on the development and function of dendritic cells [9].…”
mentioning
confidence: 99%
“…Accumulating evidence indicates that B lymphocytes exert regulatory effects on the antigen-presenting function of dendritic cells. Srini V. Kaveri and colleagues, France, have recently shown that natural antibodies sustain the differentiation and maturation of human dendritic cells, and focus in their review on the effects of therapeutic intravenous immunoglobulins on the development and function of dendritic cells [9].…”
mentioning
confidence: 99%